Genetic and morphological evidence for two species of Leucocarbo shag (Aves, Pelecaniformes, Phalacrocoracidae) from southern South Island of New Zealand. (12th February 2016) - Rawlence, Nicolas J.; Paul Scofield, R.; Spencer, Hamish G.; Lalas, Chris; Easton, Luke J.; Tennyson, Alan J. D.; Adams, Mark; Pasquet, Eric; Fraser, Cody; Waters, Jonathan M.; Kennedy, Martyn
Abstract : Leucocarbo shags are a species‐rich seabird clade exhibiting a southern circumpolar distribution. New Zealand's endemic Stewart Island shag, Leucocarbo chalconotus (G. R. Gray, 1845), comprises two regional groups (Otago and Foveaux Strait) that show consistent differences in relative frequencies between pied (black and white) and bronze (wholly dark) plumages, the extent and colour of facial carunculation, body size (based on postcranial morphometrics), and breeding season. Moreover, previous genetic research on modern and historical specimens utilizing mitochondrial DNA control‐region sequences has also shown that the Otago and Foveaux lineages may not be sister taxa; instead, in several analyses the Otago lineage is sister to the endemic Chatham Island shag, Leucocarbo onslowi (Forbes, 1893). We present new ancient DNA analyses of the type specimens for the Otago and Foveaux Strait lineages of L. chalconotus, including a phylogenetic reanalysis of the available ancient, historical, and modern control‐region sequence data for these lineages (including L. onslowi ), and additional statistical analyses incorporating new morphometric characters. These analyses indicate that under the diagnosable species concept the two lineages of Stewart Island shag represent two separate species, which we now recognize as the Otago shag, L. chalconotus (G. R. Gray, 1845), and the Foveaux shag, Leucocarbo stewarti (Ogilvie‐Grant, 1898).